PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, INTENSITAS MODAL, DAN LIKUIDITAS TERHADAP PENGHINDARAN PAJAK - Sidauruk, Tagor; Nainggolan, Adolpino; Nichmah Listiyarini (Jurnal Liabilitas, 2024)
This study aims to evaluate the impact of Corporate Social Responsibility (CSR) Disclosure, Capital Intensity, and Liquidity on Tax Avoidance practices in Manufacturing companies listed on the Indonesia Stock Exchange. The study population includes Manufacturing companies listed on the Indonesia Stock Exchange in the period 2017-2022. The sampling technique uses Purposive Sampling Approach with a total sample of 126. The data analysis method used is multiple linear regression analysis to evaluate the impact of independent variables on tax avoidance practices. The results showed that Corporate Social Responsibility and Liquidity variables had an influence on tax avoidance practices, while Capital Intensity did not have a significant impact on tax avoidance. Overall, Corporate Social Responsibility, Capital Intensity, and Liquidity simultaneously contributed 59.60% to tax avoidance, while the remaining 40.40% was influenced by other factors not included in the research model.